A política de inovação social em universidades federais do norte do Brasil à luz do institucionalismo histórico: estratégia, estrutura e mecanismos de suporte - Duarte, Michelle Matilde Semiguen Lima Trombini (2022)
This thesis is based on the premise that the University contributes effectively to the development of the regions in which they are inserted and that in a country like Brazil that has such unequal living conditions between regions, these institutions need to be socially engaged with their surroundings. In this context, social innovations emerge as an alternative, so that the knowledge produced is articulated in the face of social demands, intensifying the relationship of universities with society and expanding the fulfillment of their social mission. This research aimed to understand how the social innovation policy occurs in the Federal Universities of Northern Brazil.For this, we sought to analyze the context of social innovation under the theoretical approach of historical institutionalism, using the references proposed by Juliani (2015) : Strategy, Structure and support mechanisms.In the analysis of the strategic element, it is perceived that in the regulatory structure of all institutions there is a link with social responsibility/social transformation and the set of defined values are compatible with those associated with social innovation, thus demonstrating the strategy as an incentive to the process of social innovation.Regarding the structure, we identified limitations regarding the support structure to the projects, leading to an unfavorable scenario, presenting itself as a barrier. As for the support mechanisms, it was observed that the institutional arrangements responsible for acting as means of encouraging the search for innovative solutions to social demands are inefficient. Thus, in the context of the Federal Universities of the northern region, a significant similarity was visualized between the institutions surveyed, and it can also be said that universities still need to learn how to operationalize their social mission.